Some considerations about the diabetic macular edema - Blanca Nieve Rey Estevez; María Elena Pardo Gómez; Homero Fuentes González (Centro Provincial de Información de Ciencias Médicas, 2017)
The presence of the retinal edema is defined as an increase of liquid at histological level that causes swelling of the retina. Also, some fundamental aspects of the diabetic macular edema are exposed, such as pathophysiology, classification, epidemiologic risk factors, diagnosis and treatment.